2015
DOI: 10.3732/ajb.1500169
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, systematics, and trait evolution of Carex section Glareosae

Abstract: • Premise of the study: The circumboreal Carex section Glareosae comprises 20–25 currently accepted species. High variability in geographic distribution, ecology, cytogenetics, and morphology has led to historical problems both in species delimitation and in circumscribing the limits of the section, which is one of the major tasks facing caricologists today. • Methods: We performed phylogenetic reconstructions based on ETS, ITS, G3PDH, and matK DNA sequences from 204 samples. Concatenation of gene regions in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 96 publications
1
33
0
Order By: Relevance
“…is a species endemic to the Iberian Peninsula that belongs to Carex section Glareosae . Previous phylogenetic studies have shown this species to be monophyletic [8]. The highly specific ecological requirements of soils on acid bedrocks and very cool environments [28] explain the distribution of the species in the highest mountains of the Iberian Peninsula, never occurring below 1800 m.a.s.l.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…is a species endemic to the Iberian Peninsula that belongs to Carex section Glareosae . Previous phylogenetic studies have shown this species to be monophyletic [8]. The highly specific ecological requirements of soils on acid bedrocks and very cool environments [28] explain the distribution of the species in the highest mountains of the Iberian Peninsula, never occurring below 1800 m.a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…[6,7]), or focusing on infrageneric taxa (subgenera or sections) (e.g. [810]), the restricted geographic coverage of the studies, mostly focused on Europe and North America, and the historical non-natural classifications of the genus, are some of the causes that have hampered an extensive revision of the genus [11]. Moreover, hybridization in Carex has been proposed to limit taxonomic delimitation of species [1214].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations